Vaticano II e Igreja local: aspectos históricos e teológicos da recepção do Concílio Vaticano II na (Arqui) Diocese de Montes Claros (1966 1990) - Souza, Fábio Vieira de (2014)
This study aims to present systematically the impact and resonance of the Second Vatican Council on the Archdiocese of Montes Claros. It starts with the analysis of the conciliar event in order to better understand its internal dynamics, its meaning and the scope of its conclusive documents. Following, it presents the reception as a theological category, the theoretical framework which has allowed us to interpret the changes that occurred in this local Church in the North of State of Minas Gerais after Vatican II. Finally, it focuses on the reception of Vatican II in this Archdiocese, reporting the way that this diocesan church has received the renewing impulse of Vatican II. It presents the historical and theological factors that signaled the new attitudes of the Archdiocese of Montes Claros, and that enabled the consolidation of a Church as people of God, being active and syntonized simultaneously with the invigorating breath of Vatican II, with the guidance from the Church in Brazil and Latin America and with the social reality of the people in the north of the State of Minas Gerais